Traditional art of the peoples of the Kabardino-Balkaria: history and modern practice - Gulfiya Dz. Bazieva (Кавказология, 2024)
One of the frequently pursued purposes and objectives of modern cultural policy is to preserve and promote oral poetic traditions, as well as folk art practices in general. The purpose of the study is to determine the role of ethnoartistic traditions in modern cultural practice. The object of the analysis is the traditional art of Kabardians and Balkars in historical dynamics. The subject of the study is the study of the processes of influence of the traditions of Kabardian and Balkarian art on modern artistic creativity. In connection with the object and subject of the study, the following tasks are solved: to determine the influence of ethnic artistic traditions on modern culture, to identify the role of amateur and professional creativity in the formation of artistic self-awareness. The article reveals an inextricable link between norms, values, meanings and symbols of traditional culture, as well as the forms of their functioning and social transmission. The conclusion is drawn on the importance of a historical approach to the study of folk art as an important aspect of modern society. It has been demonstrated that traditional art, folklore, and amateur art form value orientations, foster persistent interest in national culture, and help individuals develop their creative ability. The research is scientifically original because it takes a fresh approach to studying traditional art as an autonomous entity undergoing modifications at distinct phases of its historical evolution.